Principal's Leadership Based on Sensemaking and Seizing in the Implementation of Education Policies in High School - Pelita, Pepi Januar; Ratnasari, Ana; Adiningsih, Yulia (Lembaga Penelitian dan Pendidikan Mandala, 2026)
Rapid and continuous changes in education policy have placed high schools in a complex, ambiguous, and uncertain organizational condition. In this context, school principals are not only required to ensure administrative compliance with policies, but also to interpret policies and convert them into contextual strategic decisions and actions. This study aims to analyze the process of sensemaking of school principals in understanding education policies, examine the seizing process in strategic decision-making and mobilization of school resources, and explain the relationship between sensemaking and seizing in the leadership practice of school principals.This study uses a qualitative approach with a case study design. Data was collected through in-depth interviews with principals, observation of leadership practices, and analysis of school policy documents. Data analysis is carried out in a qualitative descriptive manner through the stages of data reduction, data presentation, and conclusion drawn.The results of the study show that sensemaking plays a role as a cognitive and interpretive foundation for school principals in understanding education policy as a transformation instrument oriented to the needs of students. The seizing process can be seen in data-driven strategic decision-making, program prioritization, and allocation of school resources to support policy implementation. The linkage between sensemaking and seizing forms an adaptive leadership pattern that allows schools to respond to educational policy dynamics more effectively and sustainably. This research contributes to the development of educational leadership studies by offering a sensemaking and seizing based on school principal leadership frameworks that are relevant to the context of high schools in Indonesia.